Student COVID-19 vaccination preferences in China: A discrete choice experiment - Wang, Siyuan; Maitland, Elizabeth; Wang, Tiantian; Nicholas, Stephen; Leng, Anli (Frontiers in Public Health, 2022)
Objective: This study aims to use a Discrete Choice Experiment (DCE) questionnaire to investigate student vaccination preferences for both intrinsic and extrinsic attributes. Methods: A two-part DCE questionnaire was distributed to 1138 students through face-to-face interviews at vaccination centers in Qingdao, China. Conditional logit models were used to understand student preference trade-offs. Mixed logit models (MLM) and sub-group analysis were conducted to understanding student preference heterogeneity. Results: We found that students preferred vaccines with fewer side effects (β=0.845;95% CI,0.779-0.911), administrated through third level health facilities (β=0.170;95% CI,0.110-0.230), and had one year duration of protection (β=0.396;95% CI,0.332-0.461). Higher perception of COVID-19 risks (β=0.492;95% CI,0.432-0.552) increased the likelihood of student vaccination uptake. Surprisingly, vaccine effectiveness (60%) and percentages of acquaintances vaccinated (60%) reduced vaccination utility, the latter points to free rider problems. In addition, we find that student majors did not contribute to preference heterogeneity, and the main disparities in preferences were attributed to student risk appetites. Conclusion: Both intrinsic and extrinsic attributes were influential factors shaping student preferences for COVID-19 vaccines. Our results inform universities and local governments across China on targeting their vaccination programs.